Climate-driven Range Shifts Threaten Keystone Endemic Figs of Java: Complementing IUCN Red List Assessment with Species Distribution Modelling to Guide Conservation Priorities - Rosniati Apriani Risna; Ade Yusup Yuswandi; Dian Latifah; Damayanti Buchori; Jack Francis Plummer; Muhammad Nur Aidi; Sutomo Sutomo; Lilik Budi Prasetyo; Eimear Nic Lughadha; Angga Irfandi Yudistira (Reinwardtia, 2026)
Version 2 Note: This article was updated on 29 June 2026 to correct an omission where Angga Irfandi Yudistira as a co-author was left out of the Indonesian abstract. The author has now been added to the official author list following approval from all original authors and the editorial board. Check the updated Galley PDF RISNA, R. A., LUGHADHA, E. N., PRASETYO, L. B., SUTOMO, AIDI, M. N., BUCHORI, D., PLUMMER, J., LATIFAH, D., YUSWANDI, A. Y.  & YUDISTIRA, A. I. 2026. Climate-driven range shifts threaten keystone endemic figs of Java: complementing IUCN Red List assessment with species distribution modelling to guide conservation priorities. Reinwardtia 25(1): 49‒63. — This study evaluates the extinction risk and climate-driven habitat dynamics of two endemic figs of Java, Ficus trachycoma Miq. and F. miqueliana C.C.Berg. Both species are poorly known, with no confirmed field records for more than six decades. Conservation status was assessed under IUCN Red List criteria, with extent of occurrence (EOO) and area of occupancy (AOO) calculated using validated herbarium records. Ficus trachycoma is restricted to a single 19th-century locality, with an EOO and AOO of 4 km², a single known location, and continuing decline in habitat, qualifying it as Critically Endangered. Ficus miqueliana has been more widely recorded, with an AOO of 20 km² and an EOO of about 600 km², ≤5 locations, and continuing decline in habitat, meeting the thresholds for Endangered. Species distribution modelling using MaxEnt and CMIP6 climate projections (SSP2-4.5 and SSP5-8.5) was applied to predict current and future habitat suitability. The models performed with high accuracy (AUC = 0.912‒0.935, TSS = 1.0) and identified slope (52–73% contribution), temperature seasonality, and precipitation in the wettest, warmest, and coldest quarters as key predictors of occurrence. Ficus miqueliana’s current suitable habitat is 16,233 km² (12.4% of Java) in fragmented lowland and foothill forests. CMIP6 projections (MIROC6, SSP2-4.5/SSP5-8.5 for 2050s and 2090s) forecast net contractions with upslope shifts: mid-century losses of 9–11% in Java, late-century persistence in montane refugia under moderate emissions but severe fragmentation under high emissions. These findings demonstrate that both endemic figs are highly vulnerable to environmental change. Applying IUCN Red List assessments alongside species distribution modelling provides a replicable framework for evaluating extinction risk in data-limited species and identifies priority areas for climate-adaptive conservation planning on Java.